2021
DOI: 10.3390/en14175580
|View full text |Cite
|
Sign up to set email alerts
|

All-SiC ANPC Submodule for an Advanced 1.5 kV EV Charging System under Various Modulation Methods

Abstract: This work is focused on the design and experimental validation of the all-SiC active neutral-point clamped (ANPC) submodule for an advanced electric vehicle (EV) charging station. The topology of the station is based on a three-wire bipolar DC bus (±750 V) connecting an ac grid converter, isolated DC-DC converters, and a non-isolated DC-DC converter with a battery energy storage. Thus, in all types of power converters, the same three-level submodule may be applied. In this paper, a submodule rated at 1/3 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Several previous studies reported in [4], [5], [9]- [15] prove the effective gain in performance when WBG semiconductor devices are applied in power electronics converters, encouraging their increasing application in the industrial and academic environment. Additionally, recent studies concerning the deployment of SiC [16]- [21] and GaN [22], [23] technologies in several applications, the latter being used in high-power devices, as reported in [24].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies reported in [4], [5], [9]- [15] prove the effective gain in performance when WBG semiconductor devices are applied in power electronics converters, encouraging their increasing application in the industrial and academic environment. Additionally, recent studies concerning the deployment of SiC [16]- [21] and GaN [22], [23] technologies in several applications, the latter being used in high-power devices, as reported in [24].…”
Section: Introductionmentioning
confidence: 99%